Lipoprotein Lipase in the Brain and Nervous System - Wang, Hong (2012)
Lipoprotein lipase (LPL) is rate limiting in the provision of triglyceride-rich lipoprotein-derived lipids into tissues. LPL is also present in the brain, where its function has remained elusive. Recent evidence implicates a role of LPL in the brain in two processes: (a) the regulation of energy balance and body weight and (b) cognition. Mice with neuron-specific deletion of LPL have increases in food intake that lead to obesity, and then reductions in energy expenditure that further contribute to and sustain the phenotype. In other mice with LPL deficiency rescued from neonatal lethality by somatic gene transfer wherein LPL in the brain remains absent, altered cognition ensues. Taking into consideration data that associate LPL mutations with Alzheimer’s disease, a role for LPL in learning and memory seems likely. Overall, the time is ripe for new insights into how LPL-mediated lipoprotein metabolism in the brain impacts CNS processes and systems biology.